Modulation of Virulence Factors of Staphylococcus aureus by Nasal Decongestants. Issue 1 (2016) - Honorio, Jefferson Celli; Ribas, Cristina Rauen; Arruda, Maria Fernanda Cordeiro; Bianchini, Luiz Fernado; Campelo, Patricia Maria Stuelp; Rosa, Edvaldo Aatonio Ribeiro
No abstract available